Resilience does not mediate the association between Adverse Childhood Experiences and later life depression. Findings from The Irish Longitudinal Study on Ageing (TILDA) - Ward, Mark; Kenny, Rose; O'Halloran, Aisling; Briggs, Robert (My University, 2020)
Background: Resilience has been found to moderate the association between childhood trauma and later depression. We examined whether resilience mediates the association between Adverse Childhood Experiences (ACEs) and later life depression among older adults. Methods: Data were from The Irish Longitudinal Study on Ageing (TILDA), a prospective study of 8,500 community-dwelling adults aged ≥ 50 years. Negative binomial regressions were used to examine the relationships between ACEs, resilience, and depression and path analysis was conducted to test the potential mediating effect of resilience on the association between ACEs and depressive symptoms. Results: Mean CES-D8 depression score was 3.3 from a maximum of 24. The average resilience score from a maximum of 15 was 8.9. 26.0% of participants had experienced at least one ACE before the age of 18. A history of ACEs was associated with increased depressive symptomology. The strongest association was between physical abuse and depressive symptoms followed by sexual abuse, parental drug or alcohol use, and childhood poverty. Our path analyses showed that there was no evidence that resilience mediated the association between ACEs and depressive symptoms among this cohort. Limitations: Information on ACEs was collected retrospectively. The resilience measure depended on experience of stressful life events in the last five years and therefore some participants were excluded. Conclusions: ACEs were associated with an increased likelihood of late-life depressive symptoms. Higher resilience was associated with decreased likelihood of late-life depressive symptoms. A history of ACEs is associated with lower resilience. The association between ACEs and late-life depressive symptoms is not mediated by resilience.
PUBLISHED
Keywords: Adverse childhood experiences, Depression, older adults, resilience; Ageing; Mental Health/Psychosocial disability